(1+2)^2 = (3)^2 = 9
Yes the exponent is tied into the parentheses.
(1+2)^2 is equal to (1+2)(1+2) correct?
Again lets throw an x in to solve for,
So if you were to put a division in there 18÷(x+2)^2 = 2
Your way:
18÷(x+2)^2 = 2 18÷(x+2)(x+2) = 2 << Notice it is all multiplication and division left but do you do the division first since your going left to right? Or do you finish the simplifying the exponent (ie. The Parentheses in the original question)
18/(x+2)*(x+2)/1 = 2
18 = 2
This site uses cookies to help personalise content, tailor your experience and to keep you logged in if you register.
By continuing to use this site, you are consenting to our use of cookies.